Metabolic demands of neural-hemodynamic associated and disassociated areas in brain. Issue 10 (October 2016) - Sanganahalli, Basavaraju G; Herman, Peter; Rothman, Douglas L; Blumenfeld, Hal; Hyder, Fahmeed
Interpretation of regional blood oxygenation level-dependent (BOLD) responses in functional magnetic resonance imaging (fMRI) is contingent on whether local field potential (LFP) and multi-unit activity (MUA) is either dissociated or associated. To examine whether neural-hemodynamic associated and dissociated areas have different metabolic demands, we recorded sensory-evoked responses of BOLD signal, blood flow (CBF), and blood volume (CBV), which with calibrated fMRI provided oxidative metabolism (CMRO2 ) from rat's ventral posterolateral thalamic nucleus (VPL) and somatosensory forelimb cortex (S1FL ) and compared these neuroimaging signals to neurophysiological recordings. MUA faithfully recorded evoked latency differences between VPL and S1FL because evoked MUA in these regions were similar in magnitude. Since evoked LFP was significantly attenuated in VPL, we extracted the time courses of the weaker thalamic LFP to compare with the stronger cortical LFP using wavelet transform. BOLD and CBV responses were greater in S1FL than in VPL, similar to LFP regional differences. CBF and CMRO2 responses were both comparably larger in S1FL and VPL. Despite different levels of CBF-CMRO2 and LFP-MUA couplings in VPL and S1FL, the CMRO2 was well matched with MUA in both regions. These results suggest that neural-hemodynamic associated and dissociated areas in VPL and S1FL can have similar metabolic demands.